2017
DOI: 10.1016/j.jpowsour.2017.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the performance of a passive hybrid powerplant to power a lightweight unmanned aerial vehicle for a high altitude mission

Abstract: The objective of this research is to analyze the performance of a passive hybrid powerplant control system to be implemented in a lightweight unmanned aerial vehicle capable to ascend up to the high troposphere (10,000 m). The powerplant is based on a high-temperature PEM fuel cell connected in parallel to a set of lithium-polymer batteries and regulated by two power diodes. Test performed in steady state demonstrates that the use of the hybrid system increases the efficiency of the stack by more than 7% becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Hybrid systems may in fact hold the key in larger drone scales. [88] Increase the endurance by 300% - [89] Increase the efficiency by 3% - [67] Increased in stack efficiency of a fuel cell by 7% PV hybrid - [34] Up to 20% of the daily input can be fed through PV - [26] Fuel cell-PV (470 to 890 min for baseline conditions) i.e., is up to 90%…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid systems may in fact hold the key in larger drone scales. [88] Increase the endurance by 300% - [89] Increase the efficiency by 3% - [67] Increased in stack efficiency of a fuel cell by 7% PV hybrid - [34] Up to 20% of the daily input can be fed through PV - [26] Fuel cell-PV (470 to 890 min for baseline conditions) i.e., is up to 90%…”
Section: Discussionmentioning
confidence: 99%
“…This allows the fuel-cell system to help achieve better fuel economy and performance while part of the load is powered from the batteries or super capacitors [66]. Such combination systems have shown improvement; for example, a Li-Po battery combination with a fuel cell shows an improvement in battery stack by over 7% relative to the fuel-cell-only system [67]. Other research shows a flying time increase from 470 to 970 min [26].…”
Section: Fuel-cell-batterymentioning
confidence: 99%
See 1 more Smart Citation
“…225 The solution is to combine different power sources that can be connected either in serial, parallel, or serial-parallel in a hybrid configuration. 220 The main benefits of hybrid power systems with fuel cells compared with pure battery power systems are achieving a higher specific energy and energy density, providing redundancy in power supply, reducing the possibility of failure, improving energy efficiency, 226 and achieving higher endurance. 221 Hybrid power systems are classified as: (1) active, with control elements and (2) passive, with a direct coupling among the system components.…”
Section: Hybrid-powered Roboticsmentioning
confidence: 99%
“…A test performed to study the dynamic behavior of the p-HPP demonstrated that the presence of LiPo batteries in this configuration smooths out the sharp peaks of the current curve of the HT-PEMFC, reducing the degradation phenomena that they can induce. 220 In ref. [221], a series of tests were performed on the AeroStack hybrid, fuel-cell-based power train.…”
Section: Types Of Energy Management Systems For Hybrid Power Systemsmentioning
confidence: 99%